KAJI NUMERIK RESPONS DINAMIK WINDSHIELD PESAWAT KOMUTER 19 PENUMPANG DENGAN VARIASI JENIS MATERIAL - Qodri, Alfarizki
Efficient inter-island transportation is one of the solutions for Indonesia's problems as an archipelagic country. In last few years, Indonesian-aircraft Industries (PTDI) with National Institute of Aeronautics and Space of Indonesia (LAPAN) is developing the multipurpose N219 commuter aircraft. Aircraft development needs to go through a certification process in advance which is approved by the Directorate of Airworthiness and Aircraft Operation (DKPPU). One of the certification processes is ground test for bird strikes. This final project conducted a numerical simulation of windshield dynamic response of a 19-passenger commuter aircraft with a variety of material types. Numerical simulation was carried out using Abaqus software with several known inputs and regulations as well as modeling validation through literature studies and previous researches. The bird and windshield models were validated by comparing one of dynamic responses from previous studies. The numerical simulation shows a failure for the case of the monolithic Polymethyl methacrylate (PMMA) material which is at 4.7 mm. Thickness evaluation obtains a thickness of 14 mm in safe condition without any cracks in each area of the windshield. The study of alternative materials resulted in an evaluation of dynamic response to the available materials include Polycarbonate (PC) and PVB-coated material type as intermediate layer. Through visual deformation, maximum stress response and maximum displacement indicate that the interlayer material has better quality where non-failure conditions start at thickness of 6 mm.